An Analysis of Code Mixing Found in the Indonesian Movie: Cek Toko Sebelah - Putu Rosalina Adnyani; Sang Ayu Isnu Maharani; Putu Weddha Savitri (Program Magister Linguistik Universitas Udayana, 2023)
This study aims to 1) describe the types of code-mixing used by actors in the film